Effect of environmental enrichment on locomotor activity, habituation, learning and memory in C57BL/6 mice (Gaceta de Ciencias Veterinarias, 2019)
Environmental enrichment (EE) is a useful paradigm to increase cognition capacity and psychological well-being, as well as an adjuvant in the treatment of neurological disorders and age-related deficits. In this paper we determined the effect of EA on locomotor activity, exploration and habituation using open field test; and about memory and learning valued in the radial maze. Sample consisted of 20 C57BL/6 female mice, divided in 2 equivalent groups: Unenriched Control (CNE) housed in individual cages and Enriched Control (CE) that was housed in group for 2 months in cage that had environmental elements that stimulated exploration, locomotion, cognition and sensory organs. Results shown that mice belonging to EC group displayed a significantly higher horizontal locomotor activity during the first 3 days, with a significantly higher habituation rate, however, vertical displacements (rearing) and habituation of it did not show significantly differences between experimental groups. In the radial maze, EC group incurred in a greater number of errors in the first day (p
Keywords: Environmental enrichment; habituation; learning; memory; radial maze; open field